2020
DOI: 10.3390/rs12030583
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Diurnal Variations of Land Surface Temperatures from Numerical Weather Prediction Analyses, Infrared Satellite Estimates and In Situ Measurements

Abstract: This study evaluates the diurnal cycle of Land Surface Temperature (LST) from Numerical Weather Prediction (NWP) reanalyses (ECMWF ERA5 and ERA Interim), as well as from infrared satellite estimates (ISCCP and SEVIRI/METEOSAT), with in situ measurements. Data covering a full seasonal cycle in 2010 are studied. Careful collocations and cloud filtering are applied. We first compare the reanalysis and satellite products at continental and regional scales, and then we concentrate on comparisons with the in situ ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In addition, validation of energy balance models of surface temperature has shown that there is a tendency for such models to suffer a cold bias [37,38]. The NWP modelling technique is much more sophisticated in describing the land surface and atmospheric conditions but has been shown to struggle in accuracy with regards to surface temperatures over a variety of landcovers [39,40]. Overall, physical models as they currently exist should be further improved to act as a suitable answer on their own to the filling of LST cloud gaps, especially on large (global) scales.…”
Section: Prior Cloud Gap-filling Researchmentioning
confidence: 99%
“…In addition, validation of energy balance models of surface temperature has shown that there is a tendency for such models to suffer a cold bias [37,38]. The NWP modelling technique is much more sophisticated in describing the land surface and atmospheric conditions but has been shown to struggle in accuracy with regards to surface temperatures over a variety of landcovers [39,40]. Overall, physical models as they currently exist should be further improved to act as a suitable answer on their own to the filling of LST cloud gaps, especially on large (global) scales.…”
Section: Prior Cloud Gap-filling Researchmentioning
confidence: 99%
“…Although ECMWF recently formed the global ERA5 dataset since 1950, the one from 1950 to 1978 is not the final version. There are some evaluation and application studies on the specific elements of the datasets at home and abroad which show that the quality of the datasets is significantly improved compared with the previous version [32,41,42]. Therefore, the hourly 2 m temperature data from ERA5 during 1979-2020 are used to form daily and monthly extreme air temperatures, annual frost days (FD), and hot days (HD) in mainland China.…”
Section: Datamentioning
confidence: 99%
“…show that the quality of the dataset is signi cantly improved compared with the previous version (Zhao et al 2019;Hu et al 2019;Wang et al 2020). Therefore, the hourly 2 m temperature data from EAR5 during 1979-2020 are used to form daily and monthly extreme temperatures, annual frost days (FD) and hot days (HD) in mainland China.…”
Section: Datamentioning
confidence: 99%